Contemplating God: YHWH and Being in the Theology of St Thomas Aquinas - Levering, Matthew (Irish theological quarterly, 2002)
Aquinas's treatise on God's essence, it is argued, contemplates Israel's God metaphysically. But Aquinas's purpose is a biblical one: encountering God through contemplating, with all available intellectual resources, God's names. Aquinas thus integrates his metaphysical reflection on the name 'I am Who am' into a rich account of YHWH, Moses, the Mosaic Law, and the relationship of Christians to the contemplative life enjoyed by Moses and sustained, against various forms of idolatry, by the Mosaic Law.